Wax - Corvino, Lorenzo, 1979-; Bicocchi, Jacopo Maria; Gourvenec, Gwendolyn; Paganini, Davide, 1977-; Hauer, Rutger, 1944-; Vengeance (Firm); Leomark Studios (Firm) ([Italy] : Vengeance, 2015)
A troupe of reporters is given a video by a mysterious someone. The video is the proof left by three thirty-something, two men and a woman, of a road trip on the French Riviera, the chronicle of a week to complete an assignment before they are involved in an accident. The three share the destiny of a doomed generation. --
Originally released as a motion picture in 2015
Jacopo Maria Bicocchi, Gwendolyn Gourvenec, Davide Paganini, Muriel Gandois, Claudia Gallo, Francesca Ritrovato, Lily Bloom, Mathieu Intikalau, Andrea Renzi, Andrea Sartoretti, Rutger Hauer.
Cinematographer, Caterina Colombo, Corrado Serri ; editor, Mario Marrone ; music, Valeria Vaglio.
In Italian or English with optional English subtitles for the Italian dialogues.
Best foreign language feature film, International Filmmaker Festival of World Cinema, London, 2015
Remi Winner, 49th annual Worldfest-Houston International Film Festival, 2016
Keywords: Action and adventure films; Detective and mystery films; Horror films; Road films; Feature films; Internet videos; Streaming video